Factors Influencing the Profitability of Agricultural Cooperative Members: Case of Tuzamurane Cyeza Cooperative, Muhanga District, Rwanda - Nzamurambaho, Felicien; Ekowati, Titik; Gayatri, Siwi (Agro Ekonomi, 2024)
This study aimed to examine the influential factors that lead to the profitability of Tuzamurane Cyeza Cooperative members in Muhanga District, Rwanda. The assessment was carried out with a survey method using 120 respondents who were selected using purposive sampling. The respondents comprised 60 cooperative members and 60 non-cooperative members who were maize farmers, while 6 local leaders and staff of Tuzamurane Cyeza Cooperative were used as key informants. Data were then collected using questionnaires and interviews, followed by assessment using profitability calculation and multiple regression analysis. The assessment was carried out to analyze the effect of the independent variables (price of maize seeds, price of fertilizers, price of pesticides, wage of labor, maize production, and land lease price) on the dependent variable (the profitability of cooperative members of Tuzamurane Cyeza). The results showed that the profitability of 60 members was 13.8%, while a value of 4.9% was obtained for non-cooperative members. The value of the F-Critical (2.26) was less than the F-calculated (7.200) and the P-value (0.009) was below the significant level (0.05). This showed that the model developed in this study could be used in predicting the contribution of independent variables to the dependent variable. This study also showed that 1 coefficient (maize production) had a positive relationship with Tuzamurane Cyeza Cooperative members, while 5 coefficients (price of maize seeds, price of fertilizers, price of pesticides, wages of labor, land lease price) had an inverse association. Based on the results, all independent variables had an impact on the profitability.